2023
DOI: 10.1108/jmtm-10-2022-0376
|View full text |Cite
|
Sign up to set email alerts
|

Impact of entrepreneurial leadership on supply chain performance: the mediating role of supply chain resilience

Abstract: PurposeThe purpose of this study is to discern the role of entrepreneurial leadership (EL) – a dynamic capability – in increasing supply chain performance (SCP), through building supply chain resilience (SCR). The study further suggests that the presence of supply chain orientation (SCO) within a firm will enhance the relationship between EL and SCR.Design/methodology/approachDynamic capabilities view is used to develop the hypotheses and a survey method is used to collect data from manufacturing firms in Paki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 107 publications
(218 reference statements)
0
6
0
Order By: Relevance
“…Recent research on trends in SC management of B2B firms found SC risk and resilience as one of the key themes, highlighting the importance of studying internal drivers such as organisational culture and external drivers such as disruptions (Shrivastava, 2023). In this line, other scholars have tested how resilience can also act as a mediator of certain capabilities that impact firm performance, such as data analytics capability or entrepreneurial leadership (Bahrami et al, 2022;ul Haq and Aslam, 2023). We contributed by showing that, in the B2B context, SC resilience not only has a direct effect but also enables certain managerial attitudes to impact firm performance.…”
Section: Theoretical Contributionmentioning
confidence: 99%
“…Recent research on trends in SC management of B2B firms found SC risk and resilience as one of the key themes, highlighting the importance of studying internal drivers such as organisational culture and external drivers such as disruptions (Shrivastava, 2023). In this line, other scholars have tested how resilience can also act as a mediator of certain capabilities that impact firm performance, such as data analytics capability or entrepreneurial leadership (Bahrami et al, 2022;ul Haq and Aslam, 2023). We contributed by showing that, in the B2B context, SC resilience not only has a direct effect but also enables certain managerial attitudes to impact firm performance.…”
Section: Theoretical Contributionmentioning
confidence: 99%
“…Ali et al (2022) included ability to respond quickly, moving to new desirable state after disruption and learning from change in the variable measurement tool. Haq et al (2023) andLiu et al (2023) focused on ability to cope with change and the adaptation and flexibility to any disruptive event. Also, Hamidu et al (2023) measured SCR by including collaboration with supply chain partners, recovery to a desirable state and learning from change.…”
Section: Supply Chain Resiliencementioning
confidence: 99%
“…Moreover, many of these studies were focus on developed economies (Ciasullo et al, 2022;Liu et al, 2023;Yang & Wang, 2023;Yuan & Li, 2022) with limited focus on developing countries (Haq & Aslam, 2023;Jabbarzadeh et al, 2018;Kumar & Anbanandam, 2020).…”
Section: Research Framework and Hypothesismentioning
confidence: 99%
“…Previous research has highlighted the positive impact of manufacturing initiatives on performance, such as just-in-time and total quality management (Dieste et al. , 2021; Haq and Aslam, 2023; Hsu et al. , 2023).…”
Section: Theoretical Frameworkmentioning
confidence: 99%